2006
DOI: 10.1175/jcli3896.1
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Unified View of the American Monsoon Systems

Abstract: An important goal of the Climate Variability and Predictability (CLIVAR) research on the American monsoon systems is to determine the sources and limits of predictability of warm season precipitation, with emphasis on weekly to interannual time scales. This paper reviews recent progress in the understanding of the American monsoon systems and identifies some of the future challenges that remain to improve warm season climate prediction. Much of the recent progress is derived from complementary international pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
685
0
90

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 778 publications
(794 citation statements)
references
References 144 publications
19
685
0
90
Order By: Relevance
“…It is also observed that the vertical wind shear in the SALLJ composite reaches values of about 8 m s −1 (Figure 7(b)). This shows that the regional model used in this study detected cases of SALLJs that satisfy even the modified Bonner criteria 1, as in the SALLJ event that occurred during December 2003 in the SALLJ field experiment (Vera et al, 2006c) and was studied by Saulo et al (2007). Figure 7 shows an intensification of the wind speed observed in the global warming climate.…”
Section: Resultsmentioning
confidence: 59%
“…It is also observed that the vertical wind shear in the SALLJ composite reaches values of about 8 m s −1 (Figure 7(b)). This shows that the regional model used in this study detected cases of SALLJs that satisfy even the modified Bonner criteria 1, as in the SALLJ event that occurred during December 2003 in the SALLJ field experiment (Vera et al, 2006c) and was studied by Saulo et al (2007). Figure 7 shows an intensification of the wind speed observed in the global warming climate.…”
Section: Resultsmentioning
confidence: 59%
“…The figure also indicates the domains selected to study specific monsoonal regions (black boxes), namely the North American monsoon (e.g., Adams and Comrie, 1997;Vera et al, 2006), the South American monsoon (e.g., Vera et al, 2006;Marengo et al, 2012;Carvalho and Cavalcanti, 2016), the West Africa monsoon (e.g., Nicholson, 2013), the East African monsoon (e.g., Nairobi, 1979;Mutai and Ward, 2000), the Indian monsoon (e.g., Webster et al, 1998;Krishnamurthy and Shukla, 2000;Prasad, 2005), the East Asia monsoon (e.g., Wang et al, 2001;Yihui and Chan, 2005), and the Northern Australia monsoon (e.g., Hendon and Liebmann, 1990).…”
Section: The Onset Of the Rainy Seasonmentioning
confidence: 99%
“…-Nothofagus: native of Patagonia, >3000 km toward the south. The SASM controls the seasonal precipitation cycle in tropical South America [55][56][57][58], involving several components: the South Atlantic Convergence Zone (SACZ); the convection over the Amazon basin and the ITCZ southward shift during the boreal winter/austral summer, when most of the annual precipitation occurs southward of the Amazon River (Figure 2). However, pollen within the Coropuna glaciers reveal different air masses fluxes.…”
Section: Climatic Settingsmentioning
confidence: 99%